A New Record for Bangladesh: Nitella polycarpa Pal - Naz, Sabrina; Diba, Nasrin Jahan; Azam, Shah MGG (Journal of Life and Earth Science, 2011)
Key words: Nitella polycarpa; Characeae; new record; Bangladesh DOI: 10.3329/jles.v3i0.7446 J. Life Earth Sci., Vols. 3-4: 47-50, 2009